A One‐Pot Method to Synthesize a Co‐Based Graphene‐Like Structure Doped Carbon Material for the Oxygen Reduction Reaction. Issue 1 (26th November 2019) - Peng, Hongliang; Duan, Diancheng; Tan, Xiyou; Hu, Fang; Ma, Jiaojun; Zhang, Kexiang; Xu, Fen; Li, Bin; Sun, Lixian
Abstract: The performance of the oxygen reduction reaction (ORR) is a core issue in of fuel cells. ORR is a slow kinetic process; platinum normally is used to accelerate the reaction. This is a bottleneck for further development of fuel cells. Transition metal and heteroatom co‐doped carbon materials have great potential in ORR catalysis. However, one‐step synthesis of high activity and stability transition metal and heteroatom co‐doped electrocatalysts is still a challenge. In this work, nitrogen, fluorine, and cobalt co‐doped carbon catalyst, MPCo‐950‐5, is prepared from melamine, polytetrafluoroethylene, and cobalt acetate by a one‐step method. MPCo‐950‐5 with a graphene‐like structure and its specific surface area is 642 m 2  g −1 . The ORR half‐wave potential of MPCo‐950‐5 is positively shifted by 35 mV compared to that of commercial Pt/C. In addition, MPCo‐950‐5 also shows excellent stability and methanol tolerance. This work serves as a simple and feasible method for preparing high ORR active transition metal and heteroatom co‐doped carbon materials. Abstract : Batch cooking : A novel nitrogen, fluorine, and cobalt co‐doped graphene‐like structure carbon catalyst is prepared through a one‐pot method and it exhibits high activity for the oxygen reduction reaction in alkaline media.